Cigarette smoking, antiphospholipid antibodies and vascular events in Systemic Lupus Erythematosus. Issue 8 (1st April 2014) - Gustafsson, Johanna T; Gunnarsson, Iva; Källberg, Henrik; Pettersson, Susanne; Zickert, Agneta; Vikerfors, Anna; Möller, Sonia; Rönnelid, Johan; Elvin, Kerstin; Svenungsson, Elisabet
Abstract : Objective: Smoking can induce autoantibodies in persons who are genetically predisposed to rheumatoid arthritis. We investigated the association between smoking and antiphospholipid antibodies (aPL) in systemic lupus erythematosus (SLE), a question not previously addressed. Further, we explored the relationship between smoking, aPL and vascular events (arterial and venous, VE). Methods: In this cross-sectional study, clinical evaluation and questionnaire data were collected from 367 prevalent SLE patients. At the same time, we measured aPL (anticardiolipin (aCL), anti-β2 glycoprotein-1 (aβ2 GP1) antibodies IgG/IgM/IgA, and lupus anticoagulant (LA)), and a large set of other SLE-associated autoantibodies for comparison. Association analyses using logistic regression models with smoking, (ever, former and current with never as reference) and antibody status as outcome variable were performed. As a secondary outcome, we investigated the associations between aPL, smoking and VE. Results: In multivariable-adjusted models ever, and in particular former, cigarette smoking was associated with the most pathogenic aPL; LA, aCL IgG and aβ2 GP1 IgG. Other SLE-associated autoantibodies were not associated with smoking. The combination of smoking and aPL was strongly associated with VE. We noted a positive interaction between smoking-LA and smoking-'triple aPL' positivity for previous VE. Conclusions: We investigated a large set of commonly occurring autoantibodies in SLE, but only aPL were positively associated with a history of smoking. This association was especially apparent in former smokers. Among ever regular smokers who were aPL positive, we observed a strikingly high frequency of former VE. The underlying mechanisms and temporality between smoking, aPL and VE need further investigations.